Importance of allochthonous and autochthonous dissolved organic matter in Fe(II) oxidation: A case study in Shizugawa Bay watershed, Japan. (August 2017) - Lee, Ying Ping; Fujii, Manabu; Kikuchi, Tetsuro; Natsuike, Masafumi; Ito, Hiroaki; Watanabe, Toru; Yoshimura, Chihiro
Abstract: Ferrous iron (Fe[II]) oxidation by dissolved oxygen was investigated in the Shizugawa Bay watershed with particular attention given to the effect of dissolved organic matter (DOM) properties on Fe(II) oxidation. To cover a wide spectrum of DOM composition, water samples were collected from various water sources including freshwater (e.g., river water and wastewater effluent) and coastal seawater. Measurement of nanomolar Fe(II) oxidation by using luminol chemiluminescence under dark, air-saturated conditions at 25 °C indicated that spatio-temporal variation of the second-order rate constant (6.7–74.5 M −1  s −1 ) was partially explained by the variation of the sample pH (7.5–8.6). However, at comparable pH values, the oxidation rates for freshwater were generally greater than those for coastal seawater. The substantial decline in oxidation rate constant after the removal of humic-type (allochthonous) DOM suggested that this hydrophobic DOM is a key factor that accelerates the Fe(II) oxidation in the freshwater samples. Observed lower oxidation rates for coastal seawater compared with freshwater and organic ligand-free seawater were likely associated with microbially derived autochthonous DOM, and the variation of Fe(II) oxidation at a fixed pH was best described by fluorescence index that represents the proportion of autochthonous and allochthonous DOM in natural waters. Consistently, Fe(II) oxidation was found to be slower in the presence of cellular exudates from phytoplankton. The present study highlighted the significant effect of DOM composition on the Fe(II) oxidation in inland and coastal waters. Highlights: Fe(II) oxidation for freshwater was greater than coastal seawater. In freshwater, allochthonous (humic) DOM accelerated Fe(II) oxidation. Coastal water DOM was mostly accounted for by autochthonous (microbial) origin. Slower oxidation in coastal water was associated with autochthonous DOM.